(untitled) (Journal of Health Sciences, 2017)
Introduction: Co-existence type of ESBL-producing isolates are serious problem in the public health world. Methods Antibiotic susceptibility was determined by disc diffusion and broth microdilution according to CLSI guidelines. Double-disk synergy test was performed in order to screen for ESBLs/pAmpC beta-lactamases. PCR was used to detect blaESBL/blaampC/blacarb genes. Genetic relatedness of the strains was determined by pulsed-field-gel-electrophoresis (PFGE). Results In this study 88 of the inpatient isolates (n=126; 10.0%) and 62 of the outpatient (n=184; 6.4%) Beta-lactamase-producing isolates were taken for the study. They included 50.0/29.0% K. pneumoniae, 12.5/30.6% E. coli, 11.4/4.8% A. baumannii, 8.0/14.5% K. oxytoca, 8.0/4.8% E. cloacae, 5.7/8.1% Proteus spp., and less than 3.5% of other isolates. Co-existence of more than two type of beta-lactamases was detected in 77.3% of inpatient and 45.2% of outpatient isolates. Among inpatient isolates, Klebsiella spp. and E. coli were the most frequent isolates which produce more than two type of genes; in ≈ 65% and ≈12% cases. Separately, combination of four: TEM+SHV+CTX-M+OXA-1 beta-lactamases in inpatient K. pneumoniae isolates were detected in 63.6% cases respectively. Differents in antimicrobial resistance were higher to cephalosporins agents in Klebsiella spp., and E. coli at inpatient and outpatient isolates which produce more than two types of beta-lactamases than in isolates which produce one type of beta-lactamases. Conclusion: This work demonstrates a progressively increasing prevalence of co-existence type of beta-lactamases expecially in inpatient isolates. Continous monitoring and surveillance and proper infection control and prevention practice will limit the further spread of these isolates.